Perception of the Buying Choice of Sanitary Towels among Female Students of Caleb University, Lagos - Akin-Odukoya, Omolara; Okunade, Joshua Kayode; Akande, Emme; Serah, Chukwuemeka (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study examines the factors influencing the purchasing decisions of sanitary towels among femalestudents at Caleb University. The research aims to identify key determinants such as price, brandpreference, product quality, availability, and packaging that impact the students' choices. Data will begathered through surveys and interviews with a diverse group of female students from different academiclevels. The findings provide valuable insights into the consumer behavior of this demographic, helping totailor more effective marketing strategies for sanitary towel brands.The research explores the role of peerinfluence, advertising, and personal experiences in shaping brand loyalty among the students. Byunderstanding these elements, the study seeks to offer recommendations to manufacturers and retailers onhow to improve product offerings and marketing tactics to better meet the needs of female students atCaleb University. The results of this study will contribute to a broader understanding of consumerpreferences in the personal hygiene sector, particularly within the context of a young, educated femalepopulation.